2016
DOI: 10.1016/j.brachy.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of rectal toxicity after permanent iodine-125 seed implantation: Prospective cohort study in 2339 patients

Abstract: Rectal toxicity was relatively rare in this study compared with previous reports. For Japanese prostate cancer patients, R < 1 mL in both PI and EBRT combination therapy groups and interactive planning in EBRT combination therapy group may be effective in decreasing the incidence of rectal toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…The studies were published between 1999 and 2019, with a median sample size of 221 (IQR: 96-617) for cervical cancer and 503 (IQR: 165-2,088) for prostate cancer. The studies were carried out mostly in the United States ( n = 7, 23%) [ 19 , 35 - 37 , 40 , 41 , 47 ], followed by Taiwan ( n = 6, 20%) [ 21 - 23 , 26 , 27 , 29 ], Japan ( n = 5, 17%) [ 25 , 38 , 42 , 44 , 46 ], and South Korea ( n = 4, 13%) [ 28 , 30 , 31 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were published between 1999 and 2019, with a median sample size of 221 (IQR: 96-617) for cervical cancer and 503 (IQR: 165-2,088) for prostate cancer. The studies were carried out mostly in the United States ( n = 7, 23%) [ 19 , 35 - 37 , 40 , 41 , 47 ], followed by Taiwan ( n = 6, 20%) [ 21 - 23 , 26 , 27 , 29 ], Japan ( n = 5, 17%) [ 25 , 38 , 42 , 44 , 46 ], and South Korea ( n = 4, 13%) [ 28 , 30 , 31 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows a summary of the included prediction models. In terms of BT technique, 15 studies performed HDR-BT ( n = 13 cervix, n = 1 prostate, and n = 1 rectal cancer) [ 20 - 23 , 25 - 31 , 33 , 34 , 45 , 48 ], 13 studies used LDR-BT ( n = 12 prostate and n = 1 cervical cancer) [ 19 , 35 - 44 , 46 , 47 ], one study applied PDR-BT for cervical cancer patients [ 32 ], and one study included cervical cancer patients treated with either HDR-BT or LDR-BT [ 24 ]. Two studies (7%) excluded patients who received EBRT [ 39 , 43 ], and 11 studies (37%) included patients who were treated with chemotherapy ( n = 8 concurrent, n = 2 adjuvant, and n = 1 neoadjuvant) [ 19 , 21 - 23 , 26 - 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Grade 2 rectal bleeding rate of the combined therapy group was higher than that in previous reports from other institutions in Japan. Katayama et al [ 30 ] reported the incidence of the rectal toxicity in 2339 patients with prostate cancer undergoing 125 I brachytherapy with or without EBRT in a nationwide prospective cohort study in Japan (J-POPS). The 3-year cumulative incidences for ≥Grade 2 rectal toxicity were 2.88%, 1.76% and 6.53% in all subjects, the brachytherapy group and the EBRT combination therapy group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Harada et al [ 34 ] reported that for an RV100 kept below 1.0 ml, no Grade 2 morbidity developed in their study. Based on their results, Katayama et al [ 30 ] proposed that an RV100 of <1 ml in both brachytherapy and EBRT combination therapy groups may be effective in deceasing the incidence of rectal toxicity. Ohashi et al [ 35 ] reported that a rectal dose >160 Gy was correlated with Grade 2 rectal morbidity.…”
Section: Discussionmentioning
confidence: 99%